PURNAMA-TILEM: KONSEP RWA BHINNEDA PADA WARIGA DI BALI - Bhattacarya, Wasudewa (Institut Hindu Dharma Negeri Denpasar, 2019)
The spread of Hinduism from India to Indonesia is the result of acculturation of culture which then brought the concepts of Astronomy-Astrology in Jyoti?a to Indonesia and Bali. Arriving in Bali, the concept of Astronomy-Astrology is known as Wariga. Wariga?s existence gave rise to holy days in the implementation of Yajña. One of them is the holy day of Purnama-Tilem. The determination of this holy day is based on the appearance of the moon from the earth as a repetitive cycle. If the moon appears perfectly round from the earth, it is called Purnama (Full Moon), whereas if the moon is not visible from the earth it is called Tilem (Dark Moon). This shows that there are two very basic differences in determining Purnama and Tilem. Dualistic this difference in Hinduism is called Rwa Bhinneda. Rwa Binneda is a polarization of life that speaks of all forms of dualism such as, top down, right left, dark light, and so on. Based on manuscipts in Bali, the existence of Purnama and Tilem shows a dualism in Hindu Theology called Sanghyang Rwa Bhinneda there are Sanghyang Wulan and Sanghyang Surya at the level of Sagu?a Brahman. The dualism of the difference between Purnama and Tilem also influences Bhuwana Agung and Bhuwana Alit. The difference in the meaning of Purnama and Tilem is not something bad, but through this difference will bring about a balance between God, humans and the universe so that all beings will be able to reach the Moksartham Jagadhita ya ca iti Dharma.